High-voltage lead type aluminum electrolytic capacitor

By optimizing the materials and processes of aluminum electrolytic capacitors, their performance and service life in high temperature environments have been improved, and the problem of poor performance of existing aluminum electrolytic capacitors at high temperatures has been solved.

CN119480457APending Publication Date: 2025-02-18ZHUHAI GREE XINYUAN ELECTRONICS +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411635160.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing aluminum electrolytic capacitors perform poorly in high-temperature environments, resulting in short service life and are difficult to meet the needs of high-end applications such as new energy and electric vehicles.

Method used

By optimizing the material selection and process of cathode aluminum foil, anode aluminum foil, electrolyte and electrolytic paper, a high-voltage lead aluminum electrolytic capacitor is designed with a voltage of 400-450V, and the temperature resistance of the electrolyte is improved to above 130℃.

Benefits of technology

It significantly improves the high temperature resistance of aluminum electrolytic capacitors, so that they can maintain good performance in environments above 130°C, extend the service life and improve the reliability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480457A_ABST
    Figure CN119480457A_ABST
Patent Text Reader

Abstract

The invention discloses a high-voltage lead type aluminum electrolytic capacitor, and relates to the technical field of aluminum electrolytic capacitors. The aluminum electrolytic capacitor comprises a cathode aluminum foil, an anode aluminum foil, electrolyte and electrolytic paper, the cathode aluminum foil is obtained through formation at the formation voltage of 3-20 VF; the anode aluminum foil is obtained through formation at the formation voltage of 590-660 VF; the thickness of the electrolytic paper is 30-40 [mu] m, and the density of the electrolytic paper is 0.70-0.80 g / cm < 3 >; the temperature resistance of the electrolyte is above 130 DEG C; and the voltage of the high-voltage lead type aluminum electrolytic capacitor is 400-450 V. According to the high-voltage lead-type aluminum electrolytic capacitor provided by the invention, by optimizing the materials of the cathode aluminum foil, the anode aluminum foil, the electrolyte and the electrolytic paper, the temperature resistance of the lead-type aluminum electrolytic capacitor with the high voltage of 400-450V can be improved to 130 DEG C from the traditional 105 DEG C, so that the problem of early failure caused by the fact that the temperature suddenly exceeds 105 DEG C can be reduced, and the service life of the high-voltage lead-type aluminum electrolytic capacitor is prolonged. The product performance and the high-temperature resistance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum electrolytic capacitors, and in particular to a high-voltage lead-type aluminum electrolytic capacitor. Background Art

[0002] Leaded aluminum electrolytic capacitors are an electronic component that is mainly used to store and release electrical energy, as well as to perform filtering coupling, decoupling and phase conversion in circuits.

[0003] Leaded aluminum electrolytic capacitors are usually made of aluminum, and contain an anode (usually aluminum foil) and a cathode (usually a combination of aluminum foil and electrolyte), separated by an insulating medium. Leaded aluminum electrolytic capacitors are widely used in various electronic products and related industrial products due to their relatively low manufacturing cost, large capacity, and high voltage resistance, including consumer electronics industry, industrial power supply and lighting industry, and the rapidly developing new energy and new energy automobile industry in recent years.

[0004] In recent years, with the rapid development of emerging fields such as electric vehicles, new energy power generation, rail transportation, and advanced electromagnetic weapons, the power demand of electronic devices and electrical equipment has continued to increase. The high-temperature environment caused by high power has put forward more stringent requirements on the performance stability of electrical and electronic materials. From the perspective of technological development trends, in these cutting-edge application scenarios, high-temperature capacitors have become one of the key components to drive electrical equipment to achieve compactness, high efficiency, and large capacity.

[0005] In addition, the high temperature resistance of aluminum electrolytic capacitors currently used in China for LED driver power supply is not very good, resulting in a short service life. Generally, they will perform poorly in 1 to 2 years. This is mainly because aluminum electrolytic capacitors cannot withstand high temperatures and the product reliability is not high. With the rapid development of electronic technology, aluminum electrolytic capacitors are increasingly used in high temperature working environments. For example, high-power energy-saving lamps and electrodeless lamps in green lighting, engine control circuits in automotive electronics, etc., have put forward higher requirements for the safety, reliability, and long life of high-voltage aluminum electrolytic capacitors.

[0006] Through a sophisticated corrosion treatment process, anodized aluminum can form a micro-nano porous structure, which greatly increases the specific surface area of ​​the electrode. At the same time, its anodized aluminum oxide (AAO) dielectric layer exhibits the advantage of high breakdown field strength, allowing the capacitor to store more energy and achieve a higher energy storage density. However, the typical temperature range of aluminum electrolytic capacitors is -40°C to 85°C or 105°C, which is difficult to meet development requirements.

[0007] In the future, the aluminum electrolytic capacitor industry will show the accelerated development of high-end aluminum electrolytic capacitors, the continued growth of consumer demand for photovoltaic inverters, AI smart data centers and new energy vehicles, and the focus on high voltage, wide temperature, high capacity density and long life characteristics. Therefore, the development of high-voltage and high-temperature resistant leaded aluminum electrolytic capacitors is the key to meeting market demand, improving product performance, promoting technological development and promoting the progress of related industries. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a high temperature resistant high voltage lead type aluminum electrolytic capacitor based on the defects mentioned in the background technology to meet market demand, improve product performance, promote technological development and promote progress in related industries.

[0009] In order to solve the above problems, the present invention proposes the following technical solutions:

[0010] A high-voltage lead-type aluminum electrolytic capacitor comprises a cathode aluminum foil, an anode aluminum foil, an electrolyte and an electrolytic paper;

[0011] The cathode aluminum foil is formed by using a formation voltage of 3-20VF;

[0012] The anode aluminum foil is formed by using a formation voltage of 590-660VF;

[0013] The thickness of the electrolytic paper is 30-40 μm, and the density is 0.70-0.80 g / cm 3 ;

[0014] The temperature resistance of the electrolyte is above 130°C;

[0015] The voltage of the high-voltage lead-type aluminum electrolytic capacitor is 400-450V.

[0016] A further technical solution is that the formation voltage of the anode aluminum foil is 1.4 times or more of the working voltage.

[0017] A further technical solution is that the formation voltage of the anode aluminum foil is 1.4-1.44 times the working voltage.

[0018] A further technical solution is that the material of the electrolytic paper is at least two of wood pulp, cotton pulp, sisal fiber, agave fiber, grass fiber, and Manila hemp fiber.

[0019] A further technical solution is that the electrolytic paper has at least a two-layer structure.

[0020] A further technical solution is that the electrolytic paper has at least a four-layer structure.

[0021] A further technical solution is that the temperature resistance of the electrolyte is above 135°C.

[0022] A further technical solution is that it also includes a forming guide needle, and the forming voltage is ≥140V.

[0023] A further technical solution is that it also includes a sealing rubber plug, which contains EPDM and IIR, and the mass fraction of IIR is ≥28%.

[0024] A further technical solution is that the temperature resistance of the sealing rubber plug is above 130°C.

[0025] Compared with the prior art, the technical effects achieved by the present invention include:

[0026] The high-temperature resistant high-voltage lead-type aluminum electrolytic capacitor provided by the present invention can improve the temperature resistance of the high-voltage 400-450V lead-type aluminum electrolytic capacitor from the traditional 105°C to 130°C by optimizing the selection of cathode aluminum foil, anode aluminum foil, electrolyte and electrolytic paper, which is beneficial to reducing the early failure problem caused by the temperature suddenly exceeding 105°C, and improving product performance and high-temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0028] Figure 1 The present invention is a schematic diagram of the expanded structure of the capacitor core of the high-voltage lead-type aluminum electrolytic capacitor provided by the present invention.

[0029] Figure 2 This is a schematic structural diagram of a high-voltage lead-type aluminum electrolytic capacitor provided by the present invention.

[0030] Reference numerals

[0031] 1 cathode aluminum foil, 2 anode aluminum foil, 3 electrolytic paper, 4 guide needle, 41 positive guide needle, 42 negative guide needle, 5 sealing rubber plug, 6 aluminum shell, 7 sleeve, 10 capacitor core. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Similar component numbers in the drawings represent similar components. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0034] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.

[0035] See also Figure 1 The embodiment of the present invention provides a liquid shrink aluminum electrolytic capacitor. From the unfolded structure diagram of the capacitor core, it includes an anode aluminum foil 2, a cathode aluminum foil 1, an electrolyte, an electrolytic paper 3 and a guide pin 4. The following specifically introduces each component:

[0036] The anode aluminum foil described in the embodiment of the present invention is formed by using a formation voltage of 590-660VF.

[0037] Specifically, the preparation process of the anode aluminum foil of the embodiment of the present invention includes: plain foil-corrosion treatment-oxidation treatment-post-treatment. Among them, plain foil is a high-purity aluminum foil, and high-purity aluminum can improve the voltage resistance and stability of the capacitor. Generally speaking, the purity of the aluminum foil needs to be greater than 99.99% to ensure that the manufacturing requirements of the capacitor are met. In the process stage of plain foil preparation, it mainly includes the steps of melting, hot rolling, cold rolling, annealing and slitting: during hot pressing, hot rolling is carried out at 500-560°C, the final temperature of hot rolling is controlled at 250-300°C, the number of hot rolling passes is 17-25, and a hot-rolled coil with a thickness of 5-9 mm is obtained after hot rolling; the hot-rolled coil is cold-rolled for 3-5 times to obtain a hard aluminum foil with a thickness of 0.8-1.2 mm, and a trimming is performed at this thickness to ensure the edge quality to prevent the subsequent process from rolling and breaking. After 2-4 cold rolling passes to a hard aluminum foil with a thickness of 0.2-0.4mm, secondary trimming is performed, mainly to ensure that when the finished product thickness is rolled, there is no edge cracking and the like, to ensure a continuous strip; the annealing temperature is 400-500°C. The plain foil annealed in this temperature range can be used to obtain a finished anode foil with a higher specific capacity after corrosion and formation when the plain foil of the same thickness is used.

[0038] Furthermore, after the plain foil is prepared, the plain foil is subjected to corrosion treatment to remove the surface oil and oxide film to obtain the corroded foil, laying the foundation for the subsequent oxidation treatment. Usually, the aluminum surface is chemically treated with an alkaline solution to remove the oxide film on the surface and form a microporous structure, increase the surface area of ​​the aluminum, and increase the capacitance of the capacitor. Commonly used alkaline corrosion solutions include sodium hydroxide solutions. During the corrosion process, attention should be paid to controlling the concentration, temperature, and treatment time of the alkaline corrosion solution. Too long or too short corrosion time will affect the corrosion effect. Too short may lead to insufficient corrosion, and too long may cause excessive corrosion of the aluminum foil and reduce its mechanical properties. Controlling the concentration and temperature of the alkaline corrosion solution helps to ensure the uniformity and repeatability of the corrosion effect. The surface area, porosity, and surface roughness of the aluminum foil after corrosion treatment will affect the subsequent oxidation treatment and the performance of the capacitor. The present invention does not limit the process control of the corrosion treatment.

[0039] The corroded foil is oxidized to form a dense oxide film on the surface of the aluminum foil. This oxide film will serve as the dielectric layer of the capacitor. The thickness, uniformity and insulation properties of the oxide film have a direct impact on the performance of the capacitor. The present invention preferably uses anodizing to electrolytically oxidize the aluminum foil to generate a dielectric, i.e., formation. The formation mechanism of the oxide layer is based on electrolytic reaction. During the anodizing process, the anode foil on the roller is pulled through an electrolyte pool, and a continuous DC voltage is applied between the pool and the foil. This voltage is 135%-200% of the final rated voltage of the capacitor. The thickness of this aluminum oxide is a formation voltage of 1.4-1.5nm / V. Typically, the formation voltage of the anode foil of a 450V capacitor exceeds 600V, and the thickness of the oxide is about 900nm, which is less than one percent of a human hair.

[0040] The formation process significantly reduces the effective surface area of ​​the anode aluminum foil because the oxide occludes part of the fine microchannels. The channel etch pattern is adjusted by selecting the foil and the etching process, with low-voltage anodes having a dense channel pattern corresponding to thin oxide and high-voltage anodes having a coarse channel pattern corresponding to thick oxide.

[0041] Therefore, the degree of reaction between the aluminum foil surface and the oxygen ions in the electrolyte solution can be controlled by controlling the applied formation voltage, thereby forming a uniform and dense aluminum oxide (Al2O3) film. The chemical equation of the oxidation reaction is as follows:

[0042] 2Al+3H2O→Al2O3+6H + +6e - .

[0043] The evaluation criteria for oxidation effect include the thickness, uniformity, breakdown voltage and insulation resistance of the oxide film, among which the breakdown voltage and insulation resistance are directly related to the withstand voltage and leakage current level of the capacitor.

[0044] In the oxidation treatment process, the present invention optimizes the anode aluminum foil obtained by using a formation voltage of 590-660VF.

[0045] Furthermore, based on the fact that the voltage of the high-voltage lead-type aluminum electrolytic capacitor is 400-450V, the present invention preferably sets the formation voltage of the anode aluminum foil to be 1.4 times or more of the working voltage.

[0046] More preferably, the formation voltage of the anode aluminum foil is 1.4-1.44 times the working voltage.

[0047] Furthermore, the method further includes post-processing the oxidized aluminum foil: specifically, the oxidized aluminum foil is placed in a phosphate solution to form a dense hydration-resistant film, which covers the surface of the oxide film, and then the residual phosphate solution is cleaned and removed, and the foil is dried and cut to ensure the cleanliness and dimensional accuracy of the aluminum foil, and finally a finished anode foil is obtained. It can be understood that the hydration-resistant film layer can effectively improve the hydration resistance, and using it as an anode material to make an aluminum electrolytic capacitor can extend the service life of the aluminum electrolytic capacitor. The present invention does not limit the post-processing process.

[0048] The cathode aluminum foil described in the embodiment of the present invention is formed by using a formation voltage of 3-20VF.

[0049] Specifically, the preparation process of the cathode aluminum foil of the embodiment of the present invention includes: bare foil-pretreatment-etching-low-voltage formation-post-treatment. By controlling the formation voltage during the formation process, the insulation performance and voltage resistance of the cathode aluminum foil are improved, and the leakage current is reduced.

[0050] Specifically, there may be impurities such as grease and natural oxide layer on the surface of the original plain foil, which will affect the effect of subsequent chemical formation. Therefore, the activity of the aluminum foil surface can be increased by pre-treating the plain foil. The pre-treatment process usually includes alkaline washing, acid washing and activation. Alkaline washing refers to the use of alkaline solution to clean the surface of the aluminum foil to remove grease and other organic matter. Acid washing refers to the use of acidic solution to remove the oxide layer on the surface to expose the fresh aluminum metal surface. Activation refers to further increasing the contact angle of the aluminum foil surface by chemical or electrochemical means, thereby increasing the activity.

[0051] The etching technology is to pull the aluminum foil on the roller through the chloride solution, and apply DC and / or AC voltage between the etching solution and the aluminum foil. The etching technology dissolves aluminum on the surface of the aluminum foil, so that the surface of the entire aluminum foil forms a high-density mesh structure with billions of fine micro-channels, thereby increasing the surface area of ​​the cathode aluminum foil in contact with the electrolyte.

[0052] Generally speaking, cathode aluminum foil does not need to be formed, and can have a very high surface area and density through etching technology. However, in addition to the etching technology, the present invention further increases the contact area between the cathode aluminum foil and the electrolyte by controlling the formation voltage of 3-20VF to form the aluminum foil. The present invention does not limit the specific preparation process of the cathode aluminum foil.

[0053] In the embodiment of the present invention, the temperature resistance of the electrolyte is above 130°C.

[0054] The electrolyte is the actual cathode of the aluminum electrolytic capacitor. As the core component of the aluminum electrolytic capacitor, the service life, reliability and corresponding electrification parameters of the capacitor are closely related to the electrolyte. The quality of its performance directly affects the quality of the capacitor product. Based on the poor high temperature resistance of the electrolyte of the existing aluminum electrolytic capacitors, the aluminum electrolytic capacitors with a temperature resistance of 105°C are generally the most common on the market, and there are also some aluminum electrolytic capacitors with a temperature resistance of 125°C, which can no longer fully meet the development needs. In order to obtain a high-temperature resistant high-voltage lead-type aluminum electrolytic capacitor, the present invention requires the temperature resistance of the electrolyte to be above 130°C, and preferably an electrolyte with a temperature resistance of 135°C.

[0055] The electrolyte formula mainly consists of the following parts:

[0056] Electrolyte (lithium salt or ammonium salt):

[0057] The electrolyte in the electrolyte, that is, lithium salt or ammonium salt, is the core component, providing lithium ions and transferring lithium ions between the positive and negative electrodes of the battery. Commonly used lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), etc.

[0058] Solvent:

[0059] Solvents are mainly used as carriers for transporting lithium ions and are the component with the highest mass share in the electrolyte (about 80%). Commonly used solvents can be roughly divided into three types: carbonates, sulfites and sulfones. Carbonate products are the most widely used electrolyte solvents due to their outstanding comprehensive advantages such as performance and cost. Specifically, they include cyclic carbonate organic solvents such as ethylene carbonate (EC) and propylene carbonate (PC), as well as chain carbonate organic solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).

[0060] additive:

[0061] Additives are used in small amounts in electrolytes, but they play a very important role in improving the performance of electrolytes. The roles played by electrolyte additives in different systems are different, and the same additives in the same system play different roles in different preparation processes. Therefore, the effects of additives on electrolytes are subtle and complex. Common additives include vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sultone (1,3-PS), nitrobenzoic acid, hypophosphorous acid, nano-silica, polyethylene oxide, 8-hydroxyquinoline, polymerized borate, citric acid and diethylene glycol.

[0062] In some embodiments, the components of the electrolyte of the present invention include, by weight percentage: 33.0-45.0% solvent, 7.2-25.0% electrolyte, 12.0-18.0% additive, and the balance water.

[0063] The solvent includes ethylene carbonate.

[0064] The electrolyte includes lithium hexafluorophosphate (LiPF6), ammonium sebacate, ammonium pentaborate and ammonium isosebacate. The weight percentage of each solute in the electrolyte is: lithium hexafluorophosphate 3.5-8.5%, ammonium sebacate 0.7-1.5%, ammonium pentaborate 1.5-2.2%, ammonium isosebacate 5-8%.

[0065] The weight percentage of each additive in the electrolyte is: 0.2-1.5% of fluoroethylene carbonate, 1.2-2.0% of p-nitrobenzoic acid, 1.3-2.0% of hypophosphorous acid, 0.8-2.5% of nano silicon dioxide, 0.3-0.50% of polyethylene oxide ether, 0.2-0.40% of 8-hydroxyquinoline, 0.4-0.60% of polymerized borate, 2% of citric acid, and 3% of diethylene glycol.

[0066] The above-mentioned electrolyte is prepared with nano-scale materials, and the addition of long carbon chain branched organic ammonium salts can form a synergistic effect, greatly improving the performance of the electrolyte. While ensuring the same high conductivity and high flash voltage as other electrolytes, the temperature resistance of the electrolyte is improved to 135°C, ensuring the performance and reliability of aluminum electrolytic capacitors, and ensuring that product quality and life meet the standards.

[0067] In a specific embodiment, the electrolyte of the present invention is prepared according to the following composition in mass percentage:

[0068] Solvent: Ethylene carbonate 38%;

[0069] Electrolyte: lithium hexafluorophosphate 4.5%, ammonium sebacate 0.9%, ammonium pentaborate 1.9%, ammonium isosebacate 7%;

[0070] Additives: 0.5% fluoroethylene carbonate, 1.8% p-nitrobenzoic acid, 1.6% hypophosphorous acid, 1.1% nano-silicon dioxide, 0.3-0.50% polyethylene oxide, 0.30% 8-hydroxyquinoline, 0.50% polyborate, 2% citric acid, 3% diethylene glycol;

[0071] The balance is water.

[0072] It has been verified that the physicochemical properties and electrochemical performance of the above electrolyte are long-term stable, which makes it have a very long service life, and can improve the chemical properties of the electrolyte at high temperature, further ensuring the normal use of high-voltage lead-type aluminum electrolytic capacitors in high temperature environments.

[0073] It can be understood that the present invention does not limit the specific composition of the electrolyte. As long as its high temperature resistance is above 130°C, preferably 135°C and above, it can be used as the electrolyte of the present invention to prepare the high temperature resistant high voltage lead-type aluminum electrolytic capacitor provided by the present invention.

[0074] The high-voltage lead-type aluminum electrolytic capacitor of the present invention also optimizes the electrolytic paper: the thickness of the electrolytic paper is 30-40 μm, and the density is 0.70-0.80 g / cm 3 .

[0075] Electrolytic paper is a material made of cellulose or polyester film, whose main function is to separate and insulate the positive and negative electrodes to prevent short circuits and charge leakage.

[0076] The thickness and dielectric constant of electrolytic paper determine the capacitance of the capacitor. The greater the thickness, the greater the capacitance, and by adjusting the physical structure of the electrolytic paper and adding appropriate additives, the dielectric constant of the electrolytic paper can be increased, further increasing the capacitance.

[0077] The resistance characteristics of electrolytic paper have a great influence on the ESR of the capacitor. The resistance is mainly composed of the resistance between the conductive ions and fibers of the electrolytic paper. Lower resistance means lower ESR, which is very important for the power transfer and high-frequency response of the capacitor. Electrolytic paper should have high conductivity and low internal resistance.

[0078] The stability of electrolytic paper is also an important consideration. In the application environment of electrolytic paper, there are electrochemical reactions and chemical degradation, especially in high temperature or high voltage environments. Electrolytic paper needs to have high chemical stability and high temperature resistance to ensure the long life and reliability of the capacitor. Stable electrolytic paper can effectively resist the decomposition of electrolytes and corrosion of electrodes, keeping the performance of the capacitor unchanged.

[0079] In summary, the material of electrolytic paper, such as chemical properties and mechanical strength, has a great influence on the stability, resistance characteristics and dielectric constant of electrolytic paper.

[0080] The electrolytic paper of the present invention is preferably a multi-fiber composite electrolytic paper made of at least two cellulose raw materials, such as wood pulp, cotton pulp, sisal fiber, agave fiber, grass fiber, Manila hemp fiber, etc. Among them, Manila hemp fiber is used in the production of electrolytic capacitor paper due to its high strength, acid resistance, alkali resistance, heat resistance, and water immersion resistance.

[0081] Furthermore, the present invention preferably adopts a solution of stacking multiple layers of electrolytic paper to obtain a higher thickness. On the one hand, the stacking of multiple layers of electrolytic paper not only improves the withstand voltage, but also enables the electrolytic capacitor to have a good loss angle and low ESR (equivalent series resistance).

[0082] In the process of producing electrolytic paper, the electrical properties of the electrolytic paper can be improved by insulating the electrolytic paper.

[0083] In practical applications, the thickness and density of electrolytic paper have many specific effects on the performance of capacitors:

[0084] Capacitance: The thickness of electrolytic paper directly affects the size of the capacitor. Under the same withstand voltage conditions, generally speaking, the thicker the paper, the larger the core size, and the shorter the length of the anode foil that can be wound, resulting in a relatively smaller product capacitance.

[0085] Equivalent Series Resistance (ESR): The material, thickness, and tightness of electrolytic paper will affect its resistance characteristics, which in turn affects the ESR of the capacitor. Thicker paper may result in higher resistance, which will affect the performance of the capacitor at high frequencies. Lower ESR helps improve the power transfer capability and high-frequency response of the capacitor. Electrolytic paper with low tightness usually has lower losses because its structure is looser, which helps the flow of electrolyte and the migration of ions, thereby reducing the equivalent series resistance (ESR) of the capacitor.

[0086] Absorption: The thickness and tightness of electrolytic paper are closely related to its ability to absorb electrolyte. Paper with moderate thickness can better retain electrolyte, thereby improving the performance and stability of the capacitor. At the same time, the lower the tightness of the electrolytic paper, the better its liquid absorption performance and can absorb more electrolyte. This helps the electrolyte fully infiltrate the electrodes, thereby improving the capacitance and conductivity of the capacitor.

[0087] Mechanical strength: Thickness also affects the mechanical strength of electrolytic paper. Thicker papers generally have better tensile strength and pressure resistance, which are critical for the reliability of capacitors under working conditions. In addition, while low-density papers may provide better liquid absorption and lower losses, they may be inferior in mechanical strength. High-density papers can provide better mechanical strength, which is important for the physical stability and durability of capacitors. Further, high-density papers may provide better voltage resistance performance because their structure is more compact and less susceptible to voltage breakdown.

[0088] Thermal stability: The thickness of electrolytic paper has an impact on its thermal stability. In high temperature or high voltage environments, thicker paper may be more resistant to electrochemical reactions and chemical degradation, thereby increasing the service life of the capacitor.

[0089] Leakage current: The thickness and uniformity of electrolytic paper directly affect the leakage current of the capacitor. Paper with uneven thickness or defects may cause increased leakage current, thus affecting the performance and safety of the capacitor. Electrolytic paper with uniform tightness can provide better electrical performance and reduce the risk of short circuits inside the capacitor.

[0090] Therefore, the material, thickness and tightness of electrolytic paper are important factors affecting the performance of capacitors. Reasonable thickness and tightness design can significantly improve the electrical performance and mechanical stability of capacitors. The present invention preferably uses composite electrolytic paper made of Manila hemp fiber and wood pulp fiber, with a thickness of 30-40 μm and a tightness of 0.70-0.80 g / cm 3 The electrolytic paper under this condition can reduce the loss angle, self-heating and ESR of the high-voltage lead-type aluminum electrolytic capacitor.

[0091] The embodiment of the present invention also includes optimizing the guide needle to form the guide needle.

[0092] It can be understood that the guide pins on the outside of the aluminum electrolytic capacitor are not directly connected to the inside of the capacitor, but are connected to the aluminum foil inside the electrolytic capacitor through the guide pins. The material of the guide pins is usually iron inside and copper inside and tin outside to reduce resistance. In the capacitor, it connects the positive and negative foils and conducts current.

[0093] The properties of the guide pin material directly affect the performance of the capacitor. The guide pin material needs to have good conductivity to ensure the capacitor's conduction capacity and current transmission efficiency, while the high temperature resistance determines the capacitor's operating temperature range. Corrosion resistance, mechanical strength, etc. will also affect the stability and reliability of the capacitor. At the same time, the microstructure of the guide pin surface will also affect the performance of the capacitor.

[0094] Therefore, the present invention preferably uses a formed guide needle. That is, the formed guide needle is cleaned to remove impurities and residues on the surface to obtain a cleaned guide needle. The specific steps of the cleaning process include soaking the formed foil in a phosphoric acid aqueous solution, and then rinsing with ionized water until the phosphoric acid aqueous solution on the surface is cleaned.

[0095] The cleaned guide pin is formed to obtain a formed guide pin. The forming process is a key step in the guide pin manufacturing process, and its purpose is to form an oxide film on the surface of the guide pin to improve the performance of the capacitor. The forming process includes immersing the cleaned guide pin in a high-temperature furnace for heat treatment, and then immersing it in a mixture of ammonium dihydrogen phosphate and dipotassium hydrogen phosphate to form an oxide film.

[0096] Compared with cleaning guide pins, using chemically formed guide pins can help reduce the heat generated by the capacitor during actual use and improve the reliability of the capacitor.

[0097] See also Figure 2The cathode aluminum foil 1, electrolytic paper 3, anode aluminum foil 2, positive electrode guide pin 41, and negative electrode guide pin 42 are wound into a capacitor core 10 according to a certain structure, installed in a sleeve 7, injected with electrolyte, and sealed with a sealing rubber plug 5 to prevent the capacitor core 10 from leaking, so as to obtain a semi-finished capacitor. After the capacitor core 10 is installed in the sleeve 7, it is further transferred into an aluminum shell 6 for aging treatment, and then after sorting and testing, good products are screened out to obtain a high-voltage lead-type aluminum electrolytic capacitor.

[0098] Install the prepared high-voltage lead electrolytic capacitor on the LED power module and it can be used.

[0099] The casing has two main functions: 1) to identify the product, such as trademark, capacity, voltage, model, temperature, polarity, etc.; 2) to act as an insulator to prevent short circuit and static electricity on the pole shell.

[0100] After the capacitor bushing is processed, the present invention also includes an aging treatment for the capacitor. The specific process includes: firstly performing an aging treatment at room temperature (20-35° C.) and then performing an aging treatment at high temperature (100-130° C.).

[0101] It should be noted that, in the present invention, the sealing rubber plug contains EPDM (ethylene propylene diene monomer) and IIR (isobutylene-isoprene), and the mass fraction of IIR is ≥ 28%; and the high temperature resistance performance needs to reach above 130°C.

[0102] Specifically, the sealing rubber plug of the present invention is required to have a hardness change of no more than 5% after being placed in an environment of 135° C. for 48 hours.

[0103] The main material of the sealing rubber plug of the present invention is EPDM. By adding more than 28% by mass of isobutylene-isoprene rubber, the following properties of the sealing rubber plug can be improved:

[0104] Enhanced air tightness: IIR's low air permeability helps improve the air tightness of the seal and reduce the risk of gas leakage.

[0105] Heat aging resistance: IIR's heat aging resistance can extend the service life of the sealing ring and maintain a stable sealing effect in a high temperature environment.

[0106] Chemical resistance: IIR has good resistance to a variety of chemicals, including acids, bases and organic solvents, which enables the seal to maintain good sealing performance in harsh chemical environments.

[0107] Improved mechanical properties: The addition of IIR can improve the tensile strength, tensile stress and elasticity of the seal ring, which is essential for withstanding high-pressure environments.

[0108] Dimensional stability: IIR's low water absorption helps maintain the dimensional stability of the seal ring and prevents expansion or deformation caused by water absorption.

[0109] Electrical Insulation Properties: IIR's electrical insulation properties are very useful for sealing applications where electrical insulation is required.

[0110] For example, a sealing rubber plug containing 30% IIR by mass is selected.

[0111] In other embodiments, a sealing rubber plug containing 40% by mass of IIR is selected.

[0112] In other embodiments, a sealing rubber plug containing 50% by mass of IIR is selected.

[0113] The present invention does not limit the specific composition of the sealing rubber plug, as long as the mass fraction is ≥ 28% IIR and the performance is such that the hardness change of the rubber plug does not exceed 5% after being placed in an environment of 135°C for 48 hours. Those skilled in the art can select commercially available sealing rubber plugs with good stability and high temperature resistance according to the above requirements.

[0114] The working voltage of the high-voltage lead-type aluminum electrolytic capacitor prepared according to the embodiment of the present invention is 400-450V.

[0115] The following are the high temperature performance test results of high voltage lead type aluminum electrolytic capacitors made using cathode aluminum foil, anode aluminum foil, electrolyte and electrolytic paper of different specifications and models in the embodiments of the present invention.

[0116] Test conditions: Apply voltage (400V) at 130°C for 2000 hours. After at least 16 hours of recovery, measure whether the parameters meet the requirements.

[0117] Judgment criteria: capacity change rate ≤30%; loss angle ≤0.72; leakage current ≤108.4μA; no cracks or abnormal deformation on the appearance.

[0118] Experimental Group 1:

[0119] High voltage lead type aluminum electrolytic capacitor specification model: 400V8.2μF 8*12;

[0120] Anode aluminum foil specification model: 590-120-0.65;

[0121] Cathode aluminum foil specifications: 3-30-100;

[0122] Electrolytic paper specifications: WS280-40 / W185-20;

[0123] Electrolyte specification model: H520C;

[0124] Sealing plug model: 7.3*3.5*3.8*1.1.

[0125] Table 1 Test results of experimental group 1

[0126]

[0127]

[0128] Appearance inspection showed that all the above-mentioned high-voltage lead-type aluminum electrolytic capacitor samples had no leakage and no damage to the casing.

[0129] Experimental Group 2:

[0130] High voltage lead type aluminum electrolytic capacitor specification model: 400V8.2μF 8*12;

[0131] Anode aluminum foil specifications: 530-120-0.73;

[0132] Cathode aluminum foil specifications: 3-30-100;

[0133] Electrolytic paper specifications: WS280-40 / W185-20;

[0134] Electrolyte specification model: H520C.

[0135] Table 2 Experimental results of experimental group 2

[0136]

[0137] The withstand voltage of the anode aluminum foil of the high-voltage lead-type aluminum electrolytic capacitor in experimental group 2 is lower than that of the anode aluminum foil in experimental group 1. When the test was carried out for 1000 hours, five samples leaked, and the parameter C was small and the loss was large; the casing was not damaged.

[0138] Experimental Group 3

[0139] Based on Experimental Group 2, this experiment further investigated the effect of the forming voltage of the anode aluminum foil on the capacitor performance. The results are shown in Table 3.

[0140] The specifications of the prepared high-voltage lead-type aluminum electrolytic capacitor are 400V8.2μF 8*12. Among them,

[0141] Sample 1: The formation voltage of the anode aluminum foil is 1.32 times the working voltage of the capacitor;

[0142] Sample 2: The formation voltage of the anode aluminum foil is 1.4 times the working voltage of the capacitor;

[0143] Sample 3: The formation voltage of the anode aluminum foil is 1.5 times the working voltage of the capacitor.

[0144] Table 3 Effect of the formation voltage of the anode aluminum foil on the performance of the capacitor

[0145]

[0146] Experimental Group 4:

[0147] High voltage lead type aluminum electrolytic capacitor specification model: 400V8.2μF 8*12;

[0148] Anode aluminum foil specification model: 590-120-0.65;

[0149] Cathode aluminum foil specifications: 3-30-100;

[0150] Electrolytic paper specifications: WS280-40 / W185-20;

[0151] Electrolyte specification model: HS-452A.

[0152] Table 4 Test results of experimental group 4

[0153]

[0154] The electrolyte model selected for the high-voltage lead-type aluminum electrolytic capacitor in Experimental Group 4 is HS-452A, with a temperature resistance of 105°C. When the leakage current test was carried out for 2000h, the samples all showed leakage and became hot; the casing was not damaged.

[0155] Therefore, the preferred electrolyte model is H520C. Of course, other commercially available electrolyte models can also be used as the high-temperature resistant high-voltage lead-type aluminum electrolytic capacitor provided by the present invention, as long as its temperature resistance is above 130°C, and the better temperature resistance is above 135°C, and the temperature resistance meets the I≤(0.03CV+10)μA / 2min test.

[0156] Experimental Group 5:

[0157] High voltage lead type aluminum electrolytic capacitor specification model: 400V8.2μF 8*12;

[0158] Anode aluminum foil specification model: 590-120-0.65;

[0159] Cathode aluminum foil specifications: 3-30-100;

[0160] Electrolytic paper specifications: WM270-90;

[0161] Electrolyte specification model: H520C.

[0162] Table 5 Test results of experimental group 5

[0163]

[0164] The electrolytic paper model used for the high-voltage lead-type aluminum electrolytic capacitors in Experimental Group 5 is WM270-90, which is a double-layer electrolytic paper. The initial loss of the sample and the loss after the experiment will increase. Compared with the high-voltage lead-type aluminum electrolytic capacitors in Experimental Group 1, it is preferred to use a multi-layer composite electrolytic paper, such as a combination of models WS280-40 and W185-20.

[0165] Experimental Group 6

[0166] Based on Experimental Group 5, this experiment further investigated the effect of electrolytic paper thickness on capacitor performance. The results are shown in Table 6.

[0167] Sample 1: using double-layer 60μm thick electrolytic paper, model WS280-60;

[0168] Sample 2: using double-layer 40μm + double-layer 20μm thick electrolytic paper, model WS280-40 and W185-20;

[0169] Sample 3: Use double-layer 50μm + double-layer 20μm thick electrolytic paper, model WD270-50 and W185-20.

[0170] Table 6 Effect of electrolytic paper thickness on capacitor performance

[0171] Electrolytic paper category Capacity change rate (%) Initial loss Loss after experiment Sample 1 -22.67% 0.0732 0.3001 Sample 2 -13.57% 0.0471 0.1664 Sample 3 -10.12% 0.0418 0.1337

[0172] From the experimental results, the above conditions are all met, but considering the production cost and the initial parameter performance and the performance parameters after the experiment, the combination of WS280-40 and W185-20 is the best.

[0173] Unless otherwise specified, the sealing rubber plugs used in the experimental groups of the present invention are of the following model: 7.3*3.5*3.8*1.1. The sealing rubber plug is circular, with two small holes along the diameter. In the model, 7.3 is the diameter of the large circle, 3.5 is the thickness of the rubber plug, 3.8 is the distance between the centers of the two small holes, and 1.1 is the diameter of the small hole, all in mm.

[0174] It should be noted that the specifications of anode aluminum foil and cathode aluminum foil are named as "voltage-thickness-specific volume". Here, the specification of anode aluminum foil 590-120-0.65 is used as an example: 590 refers to the voltage resistance (VF) of the aluminum foil; 120 refers to the thickness (μm) of the foil; 0.65 refers to the specific volume (μF / cm^2) of the aluminum foil. The same is true for cathode aluminum foil.

[0175] It should be noted that the model of electrolytic paper is named according to "material layer density-thickness". Here we take WS280-60 as an example: W stands for wood pulp, S stands for sisal, 2 stands for double-layer composite paper, and 80 stands for density 0.80g / cm3 *100, 60 is thickness (μm). In other models, M is Manila hemp; D is cotton pulp.

[0176] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0177] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A high voltage lead type aluminum electrolytic capacitor, characterized in that: Including cathode aluminum foil, anode aluminum foil, electrolyte and electrolytic paper; The cathode aluminum foil is formed by using a formation voltage of 3-20VF; The anode aluminum foil is formed by using a formation voltage of 590-660VF; The thickness of the electrolytic paper is 30-40 μm, and the density is 0.70-0.80 g / cm 3 ; The temperature resistance of the electrolyte is above 130°C; The voltage of the high-voltage lead-type aluminum electrolytic capacitor is 400-450V.

2. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: The formation voltage of the anode aluminum foil is 1.4 times or more of the working voltage.

3. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: The formation voltage of the anode aluminum foil is 1.4-1.44 times the working voltage.

4. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: The electrolytic paper is made of at least two of wood pulp, cotton pulp, sisal fiber, agave fiber, grass fiber, and Manila hemp fiber.

5. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: The electrolytic paper has at least a two-layer structure.

6. The high voltage lead type aluminum electrolytic capacitor according to claim 5, characterized in that: The electrolytic paper has at least a four-layer structure.

7. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: The temperature resistance of the electrolyte is above 135°C.

8. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: Also included is a synthetic guide needle.

9. The high voltage lead type aluminum electrolytic capacitor according to claim 1, characterized in that: Also included is a sealing rubber plug, which contains IIR, and the mass fraction of IIR is ≥28%.

10. The high voltage lead type aluminum electrolytic capacitor according to claim 9, characterized in that: The temperature resistance of the sealing rubber plug is above 130°C.

Citation Information

Cited By

  • Manufacturing method of aluminum electrolytic capacitor, aluminum electrolytic capacitor and electrical equipment

    CN121506751A